Structure and thermal expansion of the low-temperature phase of SF ₂ - Isakina, A.P.; Prokhvatilov, A.I.; Rodriguez-Carvajal, J. (Физика низких температур, 2000)
Powder x-ray and neutron diffraction studies of the crystalline structure, lattice parameters and thermal expansion coefficients of sulphur hexafluoride SF₆ are performed in the temperature range 1.64-110 K. It is shown that the low-temperature phase (at T < 94.3 K) is monoclinic, space group C2/m (C2h³ ) with Z=6 in which 1/3 of molecules SF₆ occupy the positions of higher symmetry (2/m) and 2/3 of molecules - lower one (m). As follows from the analysis of obtained structural results, an availability of two types of molecular local symmetry positions is responsible for the anisotropic character of molecular rotation, peculiarities on the temperature dependences of structural and thermo-dynamic properties of SF₆ crystals at low-temperature phase, especially near Tc of orientational phase transition. It is carried out a detail comparison the present results with the known literature data.